Morphogenesis of the compartmentalizing bone around the molar primordia in the mouse mandible during dental developmental stages between lamina, bell-stage, and root formation (E13-P20) - Radlanski, Ralf J; Renz, Herbert; Zimmermann, Camilla A; Mey, Robert; Matalova, Eva (Annals of anatomy, 2015)
Despite increasing knowledge of the basic molecular aspects of bone formation and its regulation, the mechanisms of bone morphogenesis leading to a topologically specific shape remain unknown. The formation of the alveolar bone, which houses the dental primordia and later, the dental roots, may serve as a model to understand the formation of bone form in general. Thirty-eight heads of mice (C57 Bl/6J) ranging from stages E13-P20 were used to prepare histological serial sections. For each stage, virtual 3D-reconstructions were made in order to study the morphogenesis of the mandibular molar primordia concomitantly with their surrounding bone. Special focus was given to recording the remodeling pattern. It has been shown that, in early stages (E13, E14), bone formation is characterized by apposition only. In stage E15, the bony crypt around the dental primordia is remodeled mostly by resorption of bone. In stage E18, the bone remodeling pattern shows resorption all along the bony gutter, which houses the molar primordia. The medial and lateral margins are characterized by apposition. At birth (stage P0), a bony septum has begun to form between the primordium m1 and of m2, arising from both sides and characterized by pure apposition of bone. In stage P4, the crypts of m1 and m2, and also that of m3, show bone resorption inside, while the medial and lateral bony margins show apposition of bone throughout. Generally, during development, the bone gradually encapsulates the dental primordia, in such a way that the bone reaches over the dental primordia and leaves only a continuous longish opening of about 200μm width. The opening at the occlusal surface of m1, at the time of eruption, starting at stage P14, appears to have increased in size again. The distance between bone and dental primordium undergoes change during development. In erupted molars, it is around 100μm, during early developmental stages, it may be as less as 20μm. These data show the inevitability of bone remodeling.
Keywords: Animals; moláry; Morphogenesis; mandibula; Bone Development; Tooth Eruption; 3D-reconstructions; Molar; Molars; Aging; Mouse; kosti a kostní tkáň; morfogeneze; zubní kořen; Dental Occlusion; Dental primordia; Mice; Mandible; prořezávání zubů; remodelace kosti; Bone Resorption; myši; Tooth Root; počítačové zpracování obrazu; vývoj kostí; stárnutí; Bone Remodeling; resorpce kosti; zvířata; Mice, Inbred C57BL; Bone and Bones; zubní okluze; Image Processing, Computer-Assisted; Alveolar bone; myši inbrední C57BL